Pengaruh Kualitas Produk, Brand Image, dan Harga terhadap Kepuasan Konsumen pada Brand Uniqlo di Kota Semarang - Azmi Hanif; Masitha Fahmi Wardhani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of Goods Quality, Brand Image and Cost on Buyer Fulfillment with the Uniqlo brand in Semarang. A Purposive Examination Strategy was used to select 100 Uniqlo buyer respondents in the city as a test. This examination adheres to a quantitative methodology by distributing a poll containing 15 markers to respondents. Research information is split between Microsoft Success and the Factual Bundle for the Sociology (SPSS) adaptation 25 for Windows. Based on the exploratory findings, it can be assumed that Item Quality, Brand Image, and Cost exclusively impact Buyer Fulfillment. In general, the test shows that these three elements have a very big influence on Customer Fulfillment, with an importance value (sig) of 0.000 < 0.05.